Teen fatherhood, and the role as a partner and parent - Molina Gutiérrez, Rodrigo (Última Década, 2020)
This study addresses the phenomenon of teen fatherhood. It stands as a phenomenon of fatherhood exercised by an individual actor embedded in a set of family relationships. Young parents were interviewed, between 16 and 19 years of age who had a son / daughter a year or so old and had a relationship with the mother of the child. The design sample was a non-probabilistic, and the technique was a semi-structured in-depth interview. Respondents were two cities of Chile, Iquique and Santiago, both which are popular strata. The analysis performed does not distinguish subgroups in the sample. The method of analysis was the analysis of discourse. The research questions were about how fatherhood is expressed within the first year of the birth of the first son or daughter, and how they visualize the relationship in the process of adaptation to new circumstances of life.